Enhanced fluorescence properties of terbium complex/poly-l-lactic acid superfine fibers sensitized by the LSPR effect of silver nanoparticles. Issue 32 (4th April 2017) - Wen, Shipeng; Zhang, Guiming; Zhang, Rong; Zhang, Liqun; Liu, Li
Abstract : Due to the LSPR effect of Ag-NPs, the fluorescence intensity, quantum efficiency of Tb-complex in the composite fibers were improved. Abstract : In this research, Ag-NPs/Tb-complex/PLLA composite fibers with diameters of around 250 nm were successfully obtained by the electrospinning and characterized by scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and fluorescence spectra. The influence of localized surface plasmon resonance (LSPR) of silver nanoparticles (Ag-NPs) on the fluorescence of Tb(acac)3 phen/poly-l -lactic acid (Tb-complex, acac = acetylacetone; phen = phenanthroline, PLLA = poly-l -lactic acid) fibers was mainly investigated. It is found that Tb-complex dispersed in the fibers in the form of nanoclusters. The local field surrounding of Tb 3+ ions was affected by the neighboring Ag-NPs. As a result of the LSPR effect of Ag-NPs, the fluorescence intensity, quantum efficiency of Tb-complex in the composite fibers with the Ag/Tb ratio of 4 : 1, were simultaneously improved compared with the composite fibers without Ag-NPs.